1980
DOI: 10.1002/maco.19800310508
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of high‐temperature sulphide corrosion of metals and alloys

Abstract: Sulfidation appears to be considerably more suitable than oxidation for studying the high-temperature behaviour of metals. Sulfide scales are formed at considerably higher rates and at lower temperatures, in addition it is much easier to work with the radioactive sulfide isotope. The experiments can be conducted in sulfur vapour or in hydrogen fhydrogen sulfide mixtures; differences are due only to different sulfur partial pressures. Sulfide scale is formed on pure metals (e. g. Cu, Ag, N i ) as well as in bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The absence of any increased sample weight gain between 1000 h and 5000 h for the Fe-12.5Al alloy was a surprising result. This alloy exhibited the greatest degree of iron sulfide formation of all three alloys at both 500 and 5000 h. The high deviation from stoichiometry of iron sulfide allows for rapid diffusion of sulfur or base metal ions through it at high temperatures [27] and the formation of this phase usually corresponds to rapid corrosion kinetics for iron aluminum alloys [28][29][30][31][32]. The fact that the weight gain for this alloy was essentially the same at both 1000 and 5000 h suggests that the scale that formed at 1000 h was in fact protective enough to prevent further significant corrosion with prolonged exposure time.…”
Section: Discussionmentioning
confidence: 97%
“…The absence of any increased sample weight gain between 1000 h and 5000 h for the Fe-12.5Al alloy was a surprising result. This alloy exhibited the greatest degree of iron sulfide formation of all three alloys at both 500 and 5000 h. The high deviation from stoichiometry of iron sulfide allows for rapid diffusion of sulfur or base metal ions through it at high temperatures [27] and the formation of this phase usually corresponds to rapid corrosion kinetics for iron aluminum alloys [28][29][30][31][32]. The fact that the weight gain for this alloy was essentially the same at both 1000 and 5000 h suggests that the scale that formed at 1000 h was in fact protective enough to prevent further significant corrosion with prolonged exposure time.…”
Section: Discussionmentioning
confidence: 97%
“…The development of the different sulfides on the two 12.5 wt% aluminum has an important consequence on the corrosion resistance, since iron sulfide typically has a more defective structure than chromium sulfide. In a review of sulfidation of metals and alloys, Mrowec [10] reported that the maximum deviation from stoichiometry for FeS at 800°C is 0.2, while for Cr 2 S 3 at 700°C, it is 0.08. While there is a difference in temperature in the present work, and the stoichiometry of the sulfides formed here could not be determined, Mrowec's data indicates that iron sulfide will have a higher lattice defect concentration than chromium sulfide.…”
Section: Discussionmentioning
confidence: 97%
“…Burning of coal containing sulphur often leads to the formation of sulphide scales on the high-temperature components. Such scales are much less protective than oxide scales, and metal sulphidation rates are much higher than oxidation rates [5][6][7][8]. Particular attention needs to be paid to the section where highly reducing atmospheres are formed.…”
Section: Introductionmentioning
confidence: 99%